PENERAPAN ALGORITMA SUPPORT VECTOR MACHINE (SVM) DALAM PEMILIHAN BEASISWA: STUDI KASUS SMK YAPIMDA - LUKMAN LUKMAN (LPPM, 2016)
. In advance of the Nation takes generations of smart and intelligent. One important factor is education, but many students who have the ability and great potential can not attend school because they can not financially but also many students who are capable of receiving a scholarship. In the educational environment, especially schools there should be some rules or classification in determining the students who received scholarships. Therefore, in this study the algorithm Support Vector Machine (SVM) which is applied to the data the students who got beasiswa.Penelitian aims to measure the level of accuracy of SVM algorithm, in the selection of scholarship recipients in vocational YAPIMDA Jakarta. From the test results to measure the performance of the algorithm using Cross Validation testing methods, Confusion Matrix and ROC curve, it is known that the algorithm Support Vector Machine (SVM) has the highest value of accuracy is 85.82%. Keywords: Scholarship, Education, Support Vector Machine (SVM)